Application of a Gondwanan perspective to restore ecological integrity in the south-western Australian global biodiversity hotspot - Wardell-Johnson, Grant; Wardell-Johnson, Angela; Bradby, K.; Robinson, Todd; Bateman, Bill; Williams, K.; Braun, K.; Beckerling, J.; Burbridge, Michael (Blackwell Science Inc., 2016)
Bounded by ocean and desert, the isolated, predominately Mediterranean-climate region of south-western Australia (SWA) includes nine bioregions (circa 44 million hectares). The ecological integrity of the landscapes in this global biodiversity hotspot has been compromised by deforestation, fragmentation, exploitation, and introduced biota. Nature and degree of transformation varies between four interconnected landscapes (Swan Coastal Plain; South-west Forests; Wandoo Woodlands; and Great Western Woodlands). A Gondwanan perspective emphasizes a venerable biota and a cultural component to deep time. The particular importance of remnants and protected areas is recognized in restoring ecological integrity to Gondwanan landscapes. The nature and magnitude of the restoration task in these ancient, and neighboring, landscapes require higher levels of investment and more time than do recent landscapes. The protection, conservation, restoration, and rehabilitation of ecological integrity require multiple approaches in each landscape as well as consideration of the whole. Active conservation of biota and minimizing the impact of industrial- and agricultural-use are priorities. Integrating a climate focus and rethinking fire are critical restoration considerations to future trajectories under anthropogenic climate change. A legislative mandate to coordinate industrial-scale restoration and active conservation to build from protected areas must become a societal priority to restore ecological integrity.